Repertoar Musik Keroncong Dengan Menggunakan Idiom Musik Sunda: Implementasi Model Pembelajaran Kolaborasi pada Mata Kuliah Sejarah Analisis Musik Indonesia di Departemen Pendidikan Musik FPSD UPI Bandung - Hery Supiarza; Harry Tjahjodiningrat (Institut Seni Indonesia Yogyakarta, 2020)
Analysis at the Department of Music Education, FPSD, Universitas. Pendidikan Indonesia This study discusses the Implementation of Collaborative Learning Models in the History course of Indonesian music analysis at the Department of Music Education, UPI Baandung FPSD. The researcher as a lecturer in this course intends to add to the repertoire of keroncong songs, which since the 1980s keroncong song production has stalled due to competition in the Indonesian music industry. The Action Research method was used in this study to develop students' abilities in creating keroncong songs. 7 stages are used, starting from initial observation, analysis, combining ideas and ideas into big themes, evaluation exercises 1, recording and mastering. The results of this study created 10 keroncong music recordings as a product of a pure repertoire of student collaboration with the Sundanese traditional approach as the basis for creation. Future research will improve the 10 products into a more professional recording result. This research can be a reference for the application of collaborative learning models to create student work and creations in the arts.